2009
DOI: 10.1158/1535-7163.mct-08-1186
|View full text |Cite
|
Sign up to set email alerts
|

Cul3 overexpression depletes Nrf2 in breast cancer and is associated with sensitivity to carcinogens, to oxidative stress, and to chemotherapy

Abstract: Nrf2 is the key transcription factor for cytoprotective gene programs. Nrf2 is normally maintained at very low concentrations by proteasomal degradation, through its interaction with the adapter protein Keap1 and the Cul3 E3 ligase. Increased Nrf2 concentration resulting from loss of function Keap1 mutations has been described in chemoresistant non-small cell lung cancer. Previous studies in breast cancer showed low levels of some Nrf2-regulated detoxification genes, but the mechanism has not been systematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 41 publications
4
74
0
Order By: Relevance
“…2A) (26,27). Because down-regulation of Nrf2 has been found in breast cancers and is often preceded by the dysregulation of Keap1 (9,45,47), we investigated the possible relationship between these two phenomena and found that loss of miR-200a correlated with Keap1 up-regulation and Nrf2 down-regulation in breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…2A) (26,27). Because down-regulation of Nrf2 has been found in breast cancers and is often preceded by the dysregulation of Keap1 (9,45,47), we investigated the possible relationship between these two phenomena and found that loss of miR-200a correlated with Keap1 up-regulation and Nrf2 down-regulation in breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 98%
“…Nrf2 is found down-regulated in breast cancer cell lines and breast cancer patient samples when compared to healthy mammary epithelial cells (9). However, Nrf2 is not down-regulated in all cancers.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…[9][10][11] Among these seven family members, Cullin-3 and Cullin-4 have been directly linked to breast cancer. [12][13][14][15] In a study done by Chen et al Cullin-4A was shown to be amplified and overexpressed in 600PE, MDA-MB-157 and SKBR3 cells. Cullin-4A mRNA expression was detected in 14 of 30 (47%) primary breast tumors analyzed, but not in the adjacent normal breast tissues, indicating that Cullin-4A might function as an oncogene.…”
Section: Introductionmentioning
confidence: 99%
“…15 Silencing of Cullin-3, which would stabilize Nrf2, resulted in increased resistance to oxidative stress, as well as to benzo(a)pyrene, doxorubicin and paclitaxel treatments. 14 It has also been shown that a cysteine to tyrosine mutation at position 23 in Keap1 (Keap1C23Y), which functions in Cullin-3 substrate recognition, impairs the ability of Keap1 to ubiquitylate Nrf2 and repress its activity via proteasomal degradation. 15 This mutation has been found in breast cancers and suggests that the resulting Figure 4, compared with normal breast tissue, which showed no Cullin-3 expression, both tumor number 904 and tumor number 281 showed high levels of Cullin-3 protein.…”
Section: Introductionmentioning
confidence: 99%